2000
DOI: 10.1128/jvi.74.17.8166-8175.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Epstein-Barr Virus C Promoter by AUF1 and the Cyclic AMP/Protein Kinase A Signaling Pathway

Abstract: EBNA2 is an Epstein-Barr virus (EBV)-encoded protein that regulates the expression of viral and cellular genes required for EBV-driven B-cell immortalization.Elucidating the mechanisms by which EBNA2 regulates viral and cellular gene expression is necessary to understand EBV-induced B-cell immortalization and viral latency in humans. EBNA2 targets to the latency C promoter (Cp) through an interaction with the cellular DNA binding protein CBF1 (RBPJk). The EBNA2 enhancer in Cp also binds another cellular factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 73 publications
2
58
1
Order By: Relevance
“…Sequences encoded by exon 2 are important for transactivation through p40 AUF1 , although this activity may also be regulated through selected signal transduction systems (56,59). Recently, the potential for phosphorylation of p40 AUF1 at Ser 83 and Ser 87 was independently described based on in vitro kinase assays, which indicated that Ser 87 was phosphorylated by protein kinase A, whereas Ser 83 could be phosphorylated by glycogen synthase kinase-3␤, although this was dependent on prior phosphorylation of Ser 87 (60).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences encoded by exon 2 are important for transactivation through p40 AUF1 , although this activity may also be regulated through selected signal transduction systems (56,59). Recently, the potential for phosphorylation of p40 AUF1 at Ser 83 and Ser 87 was independently described based on in vitro kinase assays, which indicated that Ser 87 was phosphorylated by protein kinase A, whereas Ser 83 could be phosphorylated by glycogen synthase kinase-3␤, although this was dependent on prior phosphorylation of Ser 87 (60).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA2 regulates promoters mainly via RBPJj, and interaction with RBPJj is interrupted by NP9. However, EBNA2 tethers to some promoters like LMP1 or Cp via other transcription factors such as AUF1, 44 the Spi-1/PU.1 or Spi-B/ets family transcription factors. 45 The interaction with NP9 could exert differential effects on EBNA2 bound to these promoters via these proteins as observed in our assays.…”
Section: Infectious Causes Of Cancermentioning
confidence: 99%
“…83 Importantly, EBNA2 interacts with the transcription factor RBP-J, a protein highly conserved in evolution F from nematodes to humans F that acts downstream of the receptor Notch. 84 In Drosophila, Notch is expressed throughout development and influences cell fate decisions. Notch homologs isolated from vertebrates, including mice and humans, play a role in cell-type determination at multiple steps of differentiation, particularly in the hematopoietic system.…”
Section: Transcriptional Modulation Of B-lymphocyte Gene Expressionmentioning
confidence: 99%